A case for a Newfoundland and Labrador northern strategy. Issue 2 (3rd July 2021) - Catherine Burke, Danita
ABSTRACT: As state and sub-state actors around the world are striving to articulate their connection to, and interests in, the Arctic and the North more broadly, it is strange that the Canadian Province of Newfoundland and Labrador (NL) lacks a northern strategy of its own. NL's lack of a northern strategy is particularly strange because much of the province is Arctic and sub-Arctic. As such, this paper argues that the governments of NL (Indigenous and provincial) should start the process of creating a northern strategy for the province by coming together and signing a memorandum of understanding. This paper posits that by developing a shared strategy, the process, as well as the substance of the paper, will help the governments of the province to better understand their exclusive and shared areas of responsibility and coordination on topics of vital importance to Newfoundlanders and Labradorians, which are tied to the province's northern geography, cultures and histories.